2008
DOI: 10.1007/s11434-008-0529-5
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance in single-walled SiC nanotubes

Abstract: A two-probe system was established for a finite (7, 0) silicon carbide (SiC) nanotube coupled to Au (111) surfaces via Au-C bonds. Using the non-equilibrium Green function (NEGF) combined with density functional theory (DFT), the above system was studied for its electronic transport properties. Negative differential resistance (NDR) was observed when the bias voltage was greater than 1.4 V. Because the transport properties of the system were sensitive to the applied bias voltage, NDR might be caused by the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The NDR effect has also been reported recently in the I−V characteristics of the armchair SW-SiCNT, which has originated from the changes of density of states by the applied bias voltage. 19,20 The fluctuation of the transmission coefficient with the bias voltage is also found to be responsible for the NDR effect. 21,22 Zhang et al 23 behavior of silicon monatomic chain encapsulated in carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…The NDR effect has also been reported recently in the I−V characteristics of the armchair SW-SiCNT, which has originated from the changes of density of states by the applied bias voltage. 19,20 The fluctuation of the transmission coefficient with the bias voltage is also found to be responsible for the NDR effect. 21,22 Zhang et al 23 behavior of silicon monatomic chain encapsulated in carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al 80 investigated electronic transport properties of (4, 4) armchair SiCNT with the method combining NEGF and DFT and found the negative differential resistance (NDR) in the I-V curve of the SiCNT in the bias from +1 6 to +2 2 V. This comes from the variation in density of states (DOS) and the fluctuation of the transmission coefficient caused by the applied bias voltage. In another similar study on (7, 0) zigzag SiCNT, 78 it is reported that the current decreases when the bias is between +1 4 V and +1 7 V indicating that NDR appears in this bias range. NDR is an important property of the nanotubes for application in molecular switches and other electronic devices.…”
Section: Transport Properties Of Sicntsmentioning
confidence: 80%
“…It has been found that the asymmetric couplings of CNTs with phenyl-ethyl oligomers and pyrrollo pyrrole are responsible for NDR . The origin of the NDR effect in the I–V curve of the armchair single-walled SiCNT has been identified as being due to changes of DOS by the applied bias voltage. , In some cases, the fluctuation of the transmission coefficient with the bias voltage gives rise to the NDR effect. , …”
Section: Resultsmentioning
confidence: 99%
“…39 The origin of the NDR effect in the I−V curve of the armchair single-walled SiCNT has been identified as being due to changes of DOS by the applied bias voltage. 40,41 In some cases, the fluctuation of the transmission coefficient with the bias voltage gives rise to the NDR effect. 42,43 The computed I−V curves of (4,0)−(7,0) SiGeNTs are given in Figure 5.…”
Section: Resultsmentioning
confidence: 99%